Male principal investigators (almost) don’t publish with women in ecology and zoology - Salermo, Patricia (2019)
Representation of women in science drops substantially at each career stage, from early student to senior investigator. Disparities in opportunities for women to contribute to research metrics, such as distinguished speaker events and authorship, have been reported in many fields in the U.S.A. and Europe. However, whether female representation in scientific contributions differs in other regions, such as Latin America, is not well understood. In this study, in order to determine whether female authorship is influenced by gender or institutional location of the last (senior) author or by subfield within ecology, we gathered author information from 6849 articles in ten ecological and zoological journals that publish research articles either in or out of Latin America. We found that female authorship has risen marginally since 2002 (27 to 31%), and varies among Latin American countries, but not between Latin America and other regions. Last author gender predicted female co-authorship across all journals and regions, as research groups led by women published with over 60% female co-authors whereas those led by men published with less than 20% female co-authors. Our findings suggest that implicit biases and stereotype threats that women face in male-led laboratories could be sources of female withdrawal and leaky pipelines in ecology and zoology. Accordingly, we encourage every PI to self-evaluate their lifetime percentage of female co-authors. Female role models and cultural shifts–especially by male senior authors–are crucial for female retention and unbiased participation in science.